Growth and Biochemical Composition of Spirulina platensis Geitler in Summer Period Under the Conditions of ¦anakkale, Turkey - GOKSAN, T.; KILIC, C. (Asian Journal of Chemistry, 2010)
In present study the growth of Spirulina platensis Geitler in summer period under the conditions of Çanakkale, Turkey, was investigated. S. platensis was cultivated in raceway ponds and the cultures were kept in greenhouse. Accordingly, the percentages of chlorophyll a and phycocyanin pigments in the biomass were 0.93 ± 0.17 and 14.86 ± 0.99, respectively. Protein accounted for 59.20 ± 2.02 % whereas total lipids were 6.83 % of the dry weights. As a result, the cultivation of S. platensis in Çanakkale was successfully carried out. The climate in Canakkale is colder for outdoor cultivation of S. platensis compared to the other places where Spirulina is commercially produced in open ponds. However, the use of greenhouse was found to be effective to keep the culture temperature higher.